1993
DOI: 10.1212/wnl.43.6.1150
|View full text |Cite
|
Sign up to set email alerts
|

Environmental antecedents of young‐onset Parkinson's disease

Abstract: We conducted an exploratory study of young-onset Parkinson's disease (YOPD) to examine occupational and environmental factors associated with disease risk. This case-control study included 63 YOPD patients (diagnosis on or before age 50); controls (n = 68) were diagnosed with rheumatoid arthritis. Crude odds ratios (ORs) were computed to identify exposure variables for logistic regression analyses. After controlling for the variables of race, educational level, sex, age, age at diagnosis, and family history of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
135
0
4

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 199 publications
(145 citation statements)
references
References 0 publications
6
135
0
4
Order By: Relevance
“…A similar Danish study also reported a weak association (standardized hospitalization ratio, SHR, 1.30, 95% CI 1.03-1.63) [354]. Among 29 case-control studies that studied rural living as an exposure, 11 reported an increased risk of PD [136,141,142,147,153,289,293,303,305,309,314] with ORs ranging between 1.5 and 4.9. One study reported an inverse association [350], whereas the others found no association [131, 143-146, 154, 291, 307, 311, 312, 315, 316, 321, 325, 356-358].…”
Section: Farming Rural Living Well Water Usementioning
confidence: 88%
See 4 more Smart Citations
“…A similar Danish study also reported a weak association (standardized hospitalization ratio, SHR, 1.30, 95% CI 1.03-1.63) [354]. Among 29 case-control studies that studied rural living as an exposure, 11 reported an increased risk of PD [136,141,142,147,153,289,293,303,305,309,314] with ORs ranging between 1.5 and 4.9. One study reported an inverse association [350], whereas the others found no association [131, 143-146, 154, 291, 307, 311, 312, 315, 316, 321, 325, 356-358].…”
Section: Farming Rural Living Well Water Usementioning
confidence: 88%
“…Another population-based study reported increased risk with occupational exposure to insecticides (OR 2.05, 95% CI 1.03-4.03) [290]. Exposure to insecticides more than 10 times a year was associated with increased risk in the study of young-onset PD [153] (OR 5.75, p=0.001).…”
Section: Case-control Studiesmentioning
confidence: 96%
See 3 more Smart Citations